UST law dean sues lawyer for libel, seeks P120M in damages - Ramos, Marlon (Philippine Daily Inquirer, 2017)
UST law dean Nilo Divina has brought two libel suits against lawyer Lorna Kapunan alleging that she has maligned his reputation by linking him to the fatal hazing of Horacio Castillo III, and for making public a disbarment case that has been filed against him and 20 of his law firm associates.